Corrigendum to “Temporary immersion system, medium consistency and rooting in the micropropagation of the bamboo Dendrocalamus asper (Schult.) Backer” [South African Journal of Botany 196: 169-178, 2026] - Carolina K. Marchetti; Thiago S. Ornellas; Ricardo Bittencourt; Luis E. Oviedo Zumaque; Marcelo F. Pompelli; Miguel P. Guerra (South African Journal of Botany, 2026)

Limited functional compensation among subunits of the carbonic anhydrase module of mitochondrial complex I - Nehuen Balestieri; Fernanda Marchetti; Ana Caroline P. Martins; Danilo M. Daloso; Gabriela Pagnussat; Juan Pablo Córdoba; Eduardo Zabaleta (Planta, 2026)

Hyperspectral optical signatures of iron‐limitation in a coastal upwelling system - Sacchidanandan V. Pillai; Yayla Sezginer; Adrian Marchetti; Claire P. Till; Emily V. Speciale; Philippe D. Tortell (Limnology and Oceanography, 2026)
Iron‐limitation within the California Current System drives changes in phytoplankton taxonomic composition and photo‐physiology over a range of spatial scales. Here we demonstrate how these iron‐dependent signatures can be resolved, with high spatial resolution, using continuous ship‐board optical measurements. Deck‐board incubation experiments, along with discrete measurements of iron and macro nutrient concentrations and molecular diagnostic signatures, demonstrated contrasting levels of iron stress across our study region in the northern California Current System during summer, 2023. Photosynthetic pigment measurements indicated that phytoplankton assemblages were largely dominated by diatoms, but low and high iron waters contained differing relative abundances of phytoplankton genera with different mean cell sizes. High frequency ship‐board measurements of hyperspectral particulate absorption demonstrated the presence of two optically distinct phytoplankton assemblages that were associated with varying levels of iron stress. The distribution of the optical clusters across the cruise track showed strong coherence with a number of oceanographic and physiological variables, including phytoplankton size, nutrient drawdown ratios, photosynthetic efficiency () and absorption cross‐section (), and maximum photosynthetic rates. Notably, optical signatures explained more of the observed photo‐physiological variability than other oceanographic variables, such as sea surface temperature and chlorophyll concentration. Variability in phytoplankton iron stress appeared coupled to the age and source of the upwelling water masses. Our results demonstrate the utility of hyperspectral data to map potential iron‐stress with high spatial resolution in dynamic coastal waters.

P09-36 The toxicological effects of ultrafine particles (UFP) resulting from the combustion of fossil-based fuels and bio-fuels in an atmospheric simulation chamber - S. Marchetti; G. Motta; V. Vernocchi; G. De Falco; M. Commodo; A. D'Anna; T. Isolabella; D. Massabò; P. Minutolo; P. Prati; P. Mantecca; M. Gualtieri (Toxicology Letters, 2025)

Temporal analyses of germ cell mutations using the MutaMouse model support the recommended design in OECD test guideline 488 - Gu Zhou; Andrew Williams; Danielle P. M. LeBlanc; George R. Douglas; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2025)
The Organisation for Economic Co-operation and Development test guideline (TG) 488 uses transgenic rodent models to assess in vivo mutagenesis. TG 488 recommends 28 consecutive days of exposure with sampling of germ cells from seminiferous tubules 28 days post-exposure (i.e., 28 + 28d). We analyzed mutant frequencies (MF) in male germ cells up to 70 days post-exposure to determine whether designs other than 28 + 28d are necessary for assessing germ cell mutagenicity. Adult MutaMouse males received various doses of benzo(a)pyrene (BaP), N -ethyl- N -nitrosourea (ENU), isopropyl methanesulfonate (iPMS), or procarbazine (PRC) alongside vehicle controls for 28 days orally. Germ cells were collected from seminiferous tubules at + 3d, + 28d, + 42d, or + 70d post-exposure and MF quantified using the lacZ assay. Significant increases in lacZ MF were observed for all four chemicals at 28 + 28d. No further increases occurred at later sampling times. There was no significant effect with BaP at 28 + 3d, and a significantly stronger response with ENU and BaP at 28 + 28d compared to 28 + 3d. PRC produced the strongest response at 28 + 3d, while there was no impact of different sampling times for iPMS. Both these chemicals significantly reduced testis weight at 28 + 3d and 28 + 28d. Finally, benchmark dose modeling generated overlapping confidence intervals among the four sampling times for ENU, iPMS, and PRC. However, for BaP, the confidence interval was significantly greater at 28 + 3d than at the other sampling times. These results support the use of the 28 + 28d design as the recommended experimental design for germ cells in TG 488 and that later sampling times are not necessary.

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Predicting invasiveness of freshwater fishes imported into North America: regional differences in models and outcomes - Jennifer G. Howeth; Sarah A. Amjad; Crysta A. Gantz; Nicholas E. Mandrak; Paul L. Angermeier; Michael P. Marchetti; Julian D. Olden; David M. Lodge (Biological Invasions, 2025)
Biological invasions driven by international trade heighten the urgency for development of invasion risk models, as the traits and parameters that consistently predict successful invasion remain unresolved. For four regions of North America that include parts of the United States and Canada (Sacramento-San Joaquin River Basins, Lower Colorado River Basin, Great Lakes Region, Mid-Atlantic Region), we construct and compare classification tree models to reveal robust predictors for the establishment and ecological impact stages of freshwater fish invasion. We subsequently apply the models to identify invasive fish species in trade and conduct pathway analyses to determine which trades (aquarium, biological supply, live bait, live food, water garden) and source continents pose the greatest risk to each region. Model results differed by invasion stage and region. Across regions, establishment models shared climate-related predictors including climate match and temperature tolerance. Three of the four impact models contained prior establishment success. The greatest number of species (548) were predicted to establish in the Sacramento-San Joaquin while the fewest (5) were predicted to establish in the Mid-Atlantic. Forty species were predicted to establish in multiple regions, five of which were also predicted to have high impact. The aquarium trade and Asia supplied the most species predicted to establish. Taken together, the results highlight region-specific models, indicating no universal model predicts invasion. Climate-related and prior establishment variables were most useful to risk assessments. The regional models, and identified high-risk pathways and potential invaders, could be applied to prevent future fish invasions in North America.

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

OS01-09: Mitochondrial dysfunction trigerred by air pollution-derived ultrafine particles chronic exposure in the lungs of Balb/cJRj mice - E. Barbier; J. Carpentier; O. Simonin; A. Chaumy; W. Laine; S. Anthérieu; P. Marchetti; J.-M. Lo Guidice; J. Kluza; G. Garçon (Toxicology Letters, 2023)

Duplex sequencing provides detailed characterization of mutation frequencies and spectra in the bone marrow of MutaMouse males exposed to procarbazine hydrochloride - Annette E. Dodge; Danielle P. M. LeBlanc; Gu Zhou; Andrew Williams; Matthew J. Meier; Phu Van; Fang Yin Lo; Charles C. Valentine III; Jesse J. Salk; Carole L. Yauk; Francesco Marchetti (Archives of Toxicology, 2023)
Mutagenicity testing is an essential component of health safety assessment. Duplex Sequencing (DS), an emerging high-accuracy DNA sequencing technology, may provide substantial advantages over conventional mutagenicity assays. DS could be used to eliminate reliance on standalone reporter assays and provide mechanistic information alongside mutation frequency (MF) data. However, the performance of DS must be thoroughly assessed before it can be routinely implemented for standard testing. We used DS to study spontaneous and procarbazine (PRC)-induced mutations in the bone marrow (BM) of MutaMouse males across a panel of 20 diverse genomic targets. Mice were exposed to 0, 6.25, 12.5, or 25 mg/kg-bw/day for 28 days by oral gavage and BM sampled 42 days post-exposure. Results were compared with those obtained using the conventional lacZ viral plaque assay on the same samples. DS detected significant increases in mutation frequencies and changes to mutation spectra at all PRC doses. Low intra-group variability within DS samples allowed for detection of increases at lower doses than the lacZ assay. While the lacZ assay initially yielded a higher fold-change in mutant frequency than DS, inclusion of clonal mutations in DS mutation frequencies reduced this discrepancy. Power analyses suggested that three animals per dose group and 500 million duplex base pairs per sample is sufficient to detect a 1.5-fold increase in mutations with > 80% power. Overall, we demonstrate several advantages of DS over classical mutagenicity assays and provide data to support efforts to identify optimal study designs for the application of DS as a regulatory test.

Invasive frogs show persistent physiological differences to elevation and acclimate to colder temperatures - Jack R. Marchetti; Karen H. Beard; Emily E. Virgin; Erin L. Lewis; Steven C. Hess; Kwanho C. Ki; Layne O. Sermersheim; Adriana P. Furtado; Susannah S. French (Journal of Thermal Biology, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Antifungal activity of oils macerates of North Sardinia plants against Candida species isolated from clinical patients with candidiasis - M.G. Donadu; D. Usai; M. Marchetti; M. Usai; V. Mazzarello; P. Molicotti; M.A. Montesu; G. Delogu; S. Zanetti (Natural Product Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The iron limitation mosaic in the California Current System: Factors governing Fe availability in the shelf/near‐shelf region - C. P. Till; J. R. Solomon; N. R. Cohen; R. H. Lampe; A. Marchetti; T. H. Coale; K. W. Bruland (Limnology and Oceanography, 2019)
The California Current System is a productive eastern boundary region off the coasts of Washington, Oregon, and California. There is strong seasonality to the region, with high levels of rainfall and river input to the coastal ocean during the winter season, and coastal and Ekman upwelling during the spring and summer. Iron (Fe) input to the coastal ocean during the winter months can be stored in the continental shelf mud belts and then be delivered to the surface ocean by upwelling in the spring and summer. There have been a number of studies providing strong evidence of Fe‐limitation of diatom growth occurring in regions of the California Current System off of California, and the occurrence of Fe‐limitation has been linked with narrow continental shelf mud belt width and low river input. We provide evidence for potential Fe‐limitation of diatoms off the southern coast of Oregon in July 2014, just off the shelf break near Cape Blanco in a region with moderate shelf width and river input. Since eastern boundary regions account for a disproportionally large amount of global primary production, this observation of potential Fe‐limitation in an unexpected near‐shore region of the California Current System has implications for global models of primary productivity. In order to re‐evaluate the factors impacting Fe availability, we utilize satellite imagery to compare with historical datasets, and show that unexpected levels of Fe can often be explained by eddies, plumes of upwelled water moving offshore, or lack of recent upwelling.

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

Ecological impact of alien marine fishes: insights from freshwater systems based on a comparative review - Erik Arndt; Michael P. Marchetti; Patrick J. Schembri (Hydrobiologia, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Space-Wise approach for airborne gravity data modelling - D. Sampietro; M. Capponi; A. H. Mansi; A. Gatti; P. Marchetti; F. Sansò (Journal of Geodesy, 2017)

GTE: a new software for gravitational terrain effect computation: theory and performances - D. Sampietro; M. Capponi; D. Triglione; A. H. Mansi; P. Marchetti; F. Sansò (Pure and Applied Geophysics, 2016)

The conservation paradox of endangered and invasive species - Michael P. Marchetti; Tag Engstrom (Conservation Biology, 2016)

Dynamics of the silver fir ( Abies alba Mill.) natural regeneration in a mixed forest in the Central Apennine - G. Santopuoli; B. Lasserre; P. Di Martino; M. Marchetti (Plant Biosystems, 2016)

Ecomorphological plasticity of juvenile fall-run chinook salmon (Oncorhynchus tshawytscha) in perennial and ephemeral streams - Heather L. Bowen; Michael P. Marchetti (Environmental Biology of Fishes, 2016)

A simple multivariate analysis to assess diversity in a complex long-term managed forest area in central Italy - U. Chiavetta; B. Lasserre; P. Di Martino; M. Marchetti (Plant Biosystems, 2015)

CSF lactate for accurate diagnosis of community-acquired bacterial meningitis - S. Giulieri; C. Chapuis-Taillard; K. Jaton; A. Cometta; C. Chuard; O. Hugli; R. Du Pasquier; J. Bille; P. Meylan; O. Manuel; O. Marchetti (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Implementing REDD+ in Papua New Guinea: Can biodiversity indicators be effectively integrated in PNG's National Forest Inventory? - G. Grussu; F. Attorre; D. Mollicone; P. Dargusch; A. Guillet; M. Marchetti (Plant Biosystems, 2014)

Carbon sequestration by forests in the National Parks of Italy - M. Marchetti; L. Sallustio; M. Ottaviano; A. Barbati; P. Corona; R. Tognetti; L. Zavattero; G. Capotorti (Plant Biosystems, 2012)

A CAD/CAM-prototyped anatomical condylar prosthesis connected to a custom-made bone plate to support a fibula free flap - L. Ciocca; S. Mazzoni; M. Fantini; F. Persiani; P. Baldissara; C. Marchetti; R. Scotti (Medical & Biological Engineering & Computing, 2012)

Comparison of forest stand structure and management of silver fir–European beech forests in the Central Apennines, Italy and in the Dinaric Mountains, Slovenia - F. Lombardi; M. Klopcic; P. Di Martino; R. Tognetti; G. Chirici; A. Boncina; M. Marchetti (Plant Biosystems, 2012)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Multi‐taxon and forest structure sampling for identification of indicators and monitoring of old‐growth forest - C. Blasi; M. Marchetti; U. Chiavetta; M. Aleffi; P. Audisio; M. M. Azzella; G. Brunialti; G. Capotorti; E. Del Vico; E. Lattanzi; A. M. Persiani; S. Ravera; et al. (Plant Biosystems, 2010)

Linking taxonomical and functional biodiversity of saproxylic fungi and beetles in broad‐leaved forests in southern Italy with varying management histories - A. M. Persiani; P. Audisio; D. Lunghini; O. Maggi; V. M. Granito; A. B. Biscaccianti; U. Chiavetta; M. Marchetti (Plant Biosystems, 2010)

Iron and silicic acid effects on phytoplankton productivity, diversity, and chemical composition in the central equatorial Pacific Ocean - Adrian Marchetti; Diana E. Varela; Veronica P. Lance; Veronica P. Lance; Matteo Palmucci; Mario Giordano; E. Virginia Armbrust (Limnology and Oceanography, 2010)
A microcosm nutrient‐amendment experiment using central equatorial Pacific Ocean (0°, 140°W) mixed‐layer waters was conducted to determine biogeochemical controls on phytoplankton with an emphasis on post‐iron enrichment nutrient uptake dynamics and species composition. The addition of either Fe (termed Fe‐only) or Fe and Si(OH) 4 (termed FeSi) to on‐deck incubations resulted in growth primarily of pennate diatoms, with statistically equivalent increases relative to the control in maximum photochemical efficiency, chlorophyll a (Chl a ) concentrations, particulate organic carbon and nitrogen concentrations, and dissolved inorganic carbon uptake rates. In contrast, at peak Chl a concentrations, there was a 3.4‐fold higher abundance of large diatoms and a 3.9‐ fold lower abundance of small pennate diatoms in FeSi relative to Fe‐only, which translated into a 3.5‐fold higher Si(OH) 4 uptake rate and a 2.1‐fold higher biogenic silica concentration. Fourier transform infrared spectroscopy indicated that relative to cells from Fe‐only, cells from FeSi possessed the lowest protein : carbohydrate ratios, and ratios of lipids, proteins, and carbohydrates relative to silica, consistent with differences in diatom C allocation or increased silicification or both. Our results suggest that after Fe addition, diatom organic matter accumulation rates (i.e., C and N uptake rates) are enhanced but the low, ambient [Si(OH) 4 ] retards cell division rates, resulting in fewer large diatoms with relatively high C and N contents. After the simultaneous addition of Fe and Si(OH) 4 , enhanced rates of diatom organic matter accumulation and cell division results in more large, heavily silicified diatoms with relatively low C and N contents.

Juvenile Chinook salmon (Oncorhynchus tshawytscha) growth in off-channel and main-channel habitats on the Sacramento River, CA using otolith increment widths - Michael P. Limm; Michael P. Marchetti (Environmental Biology of Fishes, 2009)

Influence of biochemical, mineral and morphological features of natural food on tropical cladocerans - Claudia Fileto; Marlene S. Arcifa; Juliana M. Marchetti; Izabel C. Turati; Norberto P. Lopes (Aquatic Ecology, 2007)

Outlining multi-purpose forest inventories to assess the ecosystem approach in forestry - P. Corona; M. Marchetti (Plant Biosystems, 2007)

ForestBIOTA data on deadwood monitoring in Europe - D. Travaglini; A. Barbati; G. Chirici; F. Lombardi; M. Marchetti; P. Corona (Plant Biosystems, 2007)

Distinguishing between Invasions and Habitat Changes as Drivers of Diversity Loss among California's Freshwater Fishes - THEO LIGHT; MICHAEL P. MARCHETTI (Conservation Biology, 2007)
Many of California's native populations of freshwater fish are in serious decline, as are freshwater faunas worldwide. Habitat loss and alteration, hydrologic modification, water pollution, and invasions have been identified as major drivers of these losses. Because these potential causes of decline are frequently correlated, it is difficult to separate direct from indirect effects of each factor and to appropriately rank their importance for conservation action. Recently a few authors have questioned the conservation significance of invasions, suggesting that they are “passengers” rather than “drivers” of ecological change. We compiled an extensive, watershed‐level data set of fish presence and conservation status, land uses, and hydrologic modifications in California and used an information theoretic approach (Akaike's information criterion, AIC) and path analysis to evaluate competing models of native fish declines. Hydrologic modification (impoundments and diversions), invasions, and proportion of developed land were all predictive of the number of extinct and at‐risk native fishes in California watersheds in the AIC analysis. Although nonindigenous fish richness was the best single predictor (after native richness) of fishes of conservation concern, the combined ranking of models containing hydrologic modification variables was slightly higher than that of models containing nonindigenous richness. Nevertheless, the path analysis indicated that the effects of both hydrologic modification and development on fishes of conservation concern were largely indirect, through their positive effects on nonindigenous fish richness. The best‐fitting path model was the driver model, which included no direct effects of abiotic disturbance on native fish declines. Our results suggest that, for California freshwater fishes, invasions are the primary direct driver of extinctions and population declines, whereas the most damaging effect of habitat alteration is the tendency of altered habitats to support nonindigenous fishes.

A forest typology for monitoring sustainable forest management: The case of European Forest Types - A. Barbati; P. Corona; M. Marchetti (Plant Biosystems, 2007)

Effects of Hatchery Rearing on Brain Structures of Rainbow Trout, Oncorhynchus mykiss - Michael P. Marchetti; Gabrielle A. Nevitt (Environmental Biology of Fishes, 2003)

Linear and non-linear analysis of surface electromyograms in weightlifters - F. Felici; A. Rosponi; P. Sbriccoli; G.C. Filligoi; L. Fattorini; M. Marchetti (European Journal of Applied Physiology, 2001)

Spatial and Temporal Ecology of Native and Introduced Fish Larvae in Lower Putah Creek, California - Michael P. Marchetti; Peter B. Moyle (Environmental Biology of Fishes, 2000)

The effect of urea and pig slurry fertilization on denitrification, direct nitrous oxide emission, volatile fatty acids, water-soluble carbon and anthrone-reactive carbon in maize-cropped soil from the Po plain (Modena, Italy) - P. G. Arcara; C. Gamba; D. Bidini; R. Marchetti (Biology and Fertility of Soils, 1999)

An Experimental Study of Competition Between the Native Sacramento Perch (Archoplites interruptus) and Introduced Bluegill (Lepomis macrochirus) - Michael P. Marchetti (Biological Invasions, 1999)

Evidence for gene conversion in the generation of extensive polymorphism in the promoter of the growth hormone gene - Mara Giordano; Cristina Marchetti; Elena Chiorboli; Gianni Bona; P. Momigliano Richiardi (Human Genetics, 1997)

Apoptosis of cells lacking mitochondrial DNA - P. Marchetti; N. Zamzami; S. A. Susin; P. X. Petit; G. Kroemer (Apoptosis, 1996)